2010
DOI: 10.1186/1755-8794-3-41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bacterial diversity of Pressure ulcers using bTEFAP pyrosequencing

Abstract: BackgroundDecubitus ulcers, also known as bedsores or pressure ulcers, affect millions of hospitalized patients each year. The microflora of chronic wounds such as ulcers most commonly exist in the biofilm phenotype and have been known to significantly impair normal healing trajectories.MethodsBacterial tag-encoded FLX amplicon pyrosequencing (bTEFAP), a universal bacterial identification method, was used to identify bacterial populations in 49 decubitus ulcers. Diversity estimators were utilized and wound com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 49 publications
3
95
1
1
Order By: Relevance
“…The tissue of all chronic wounds is colonized by polymicrobial flora (Smith et al, 2010). Over 90% of chronic wounds contain bacteria and fungi from the skin, oral mucosa, enteric tract or environment.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue of all chronic wounds is colonized by polymicrobial flora (Smith et al, 2010). Over 90% of chronic wounds contain bacteria and fungi from the skin, oral mucosa, enteric tract or environment.…”
Section: Introductionmentioning
confidence: 99%
“…It differs from the classic Sanger sequencing, in that it relies on the detection of pyrophosphate release upon nucleotide incorporation, rather than chain termination with dideoxynucleotides (Ronaghi et al, 1998). This deep sequencing technique has been used to evaluate the diversity of microbial populations where thousands of reads/sequences can be www.intechopen.com Skin Grafts -Indications, Applications and Current Research 280 obtained from each sample (Andersson et al, 2007;Bogaert et al;Dowd et al, 2008;Price et al, 2010;Smith et al, 2010;Stewart et al, 2010;Wolcott et al, 2009). …”
Section: Pyrosequencingmentioning
confidence: 99%
“…In a retrospective analysis of the DNA resulting from the wounds included in the study, qPCR with universal fungal primers and probe revealed fungal DNA in one of 14 samples. In a recent study by Smith (2010) pyrosequencing was used to identify bacterial populations in 49 pressure ulcers. Diversity estimators were utilized and wound community compositions analyzed in relation to metadata such as age, race, gender, and comorbidities.…”
Section: Microbial Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Culture results must be interpreted with caution, because should not be used as the sole criterion for infections, without clinical or histopathological evidence of infection (Hirshberg J & Al, 2000). Despite the aforementioned information, there is agreement on the most frequently isolated bacteria, including Staphylococcus aureus, betaHemolytic Streptococci, Gram negative organisms (including Enterobacteriaceae and Pseudomonas spp, and other Gram positive organisms such Enterococcus spp) and Anaerobic organisms (Chow AW & Al, 1977;Sapico FI & Al, 1986;Muder RR & Al, 1992;Nicolle LE & Al, 1994b;Smith DM & Al, 2010;Lund-Nielsen B & Al, 2011 …”
Section: Pressure Ulcersmentioning
confidence: 99%